Manajemen Peserta Didik sebagai Strategi Meningkatkan Prestasi Siswa dan Kualitas Sekolah - Oktavia, Nadia; Avrillia Nesya Savitri; Rahmadania Octavia; Anindita Cahya Pratama; Ayu Wulandari (Jurnal Ilmu Pendidikan dan Sosial, 2025)
The purpose of this study was to determine how Al-Furqon High School implements student management, so that later students at Al-Furqon High School can improve student achievement and at the same time improve the quality of the school. Through planning, organizing, supervision, and evaluation, with the main focus being on monitoring student activities as a whole, both outside and inside the classroom. This analysis includes guidance and counseling services, outdoor and indoor learning, student discipline, and student involvement in extracurricular activities, which will later support student talents and potential both in academic and non-academic fields. The principal, BK teacher, homeroom teacher, and students are the subjects of the study. This research method uses a qualitative research approach and collects data through observation, documentation, and interviews. Primary data sources are taken through direct observation results in the field, recordings of interview results that are first converted into word form and then we draw conclusions. Meanwhile, secondary data is taken through journals, books, and official school documents such as learning outcomes. The collected data is then analyzed through several stages which will later make it easier to draw conclusions. The results of the study theoretically show that organized student management with teacher supervision, communication between teachers and parents, and student involvement in school activities greatly contribute to student achievement and school quality. Practically, this study can be a guide for schools to improve student management, by increasing communication between teachers and parents, and designing programs to support student academic success and improve school quality.